2013
DOI: 10.1194/jlr.m039644
|View full text |Cite
|
Sign up to set email alerts
|

LDL particle core enrichment in cholesteryl oleate increases proteoglycan binding and promotes atherosclerosis

Abstract: the pathophysiology of atherosclerosis ( 2 ). After LDL particles enter the intima of the artery wall, they can interact with proteoglycans, which are structural proteins residing in the extracellular matrix that consist of one or more glycosaminoglycan (GAG) side-chains attached to core proteins. The LDL-proteoglycan complex is generally regarded as an electrostatic interaction ( 3 ). The sulfation pattern of the acidic sugar groups that form the GAG chains on the proteoglycans results in an overall negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 42 publications
3
35
1
Order By: Relevance
“…5,6,[46][47][48][49][50][51] The results strongly support the strong atherogenicity of saturated fatty acids through effects to raise LDL cholesterol concentrations compared with the effects of n-6 polyunsaturated fatty acids. Although monounsaturated fatty acids promoted atherosclerosis despite lowering LDL cholesterol, mechanisms related to LDL binding to proteoglycan may differ in humans.…”
Section: Clinical Statements and Guidelinessupporting
confidence: 50%
See 1 more Smart Citation
“…5,6,[46][47][48][49][50][51] The results strongly support the strong atherogenicity of saturated fatty acids through effects to raise LDL cholesterol concentrations compared with the effects of n-6 polyunsaturated fatty acids. Although monounsaturated fatty acids promoted atherosclerosis despite lowering LDL cholesterol, mechanisms related to LDL binding to proteoglycan may differ in humans.…”
Section: Clinical Statements and Guidelinessupporting
confidence: 50%
“…49 Atherosclerosis extent has consistently been positively correlated with high LDL proteoglycan binding affinity. 48,50 Finally, a diet typical of the 1980s in the United States, high in saturated fat, fed to rhesus monkeys for 2 years increased serum cholesterol to 383 mg/dL and caused atherosclerosis that had complex pathological features similar to atherosclerosis in young human adults who died of trauma. 51 In contrast, a "prudent" diet recommended by the AHA to prevent CHD, low in saturated and high in polyunsaturated fat, produced lower serum cholesterol levels, 199 mg/dL, and less atherosclerosis.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…Excessive circulating apoB-containing lipoproteins, especially LDL, would be retained in the arterial intima 6 and may initiate atherogenesis. SOAT2 knockout animals have delayed atherosclerosis development that is presumably due to the loss of capability of esterification of cholesterol oleate and packaging of those cholesterol esters into potentially atherogenic lipoprotein particles.…”
Section: Discussionmentioning
confidence: 99%
“…SOAT subtype1 (SOAT1) is expressed in a variety of tissues while SOAT subtype2 (SOAT2) is expressed preferentially in enterocytes of the intestine and hepatocytes of the liver 2 , where one of its roles is to generate CE for packaging into chylomicrons and very low-density lipoproteins (VLDL), respectively 3, 4 . Cholesterol esters, especially cholesterol oleate, are major components of atherogenic lipoproteins, appearing to play a critical role in the pathogenesis of atherosclerosis 5, 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that SOAT2 KO versus WT mice or mice fed FO versus monounsaturated fat had plasma LDL enriched in PUFA CE species and bound with less affi nity to proteoglycans, suggesting a mechanism by which apoB lipoproteins from mice fed dietary PUFA may be less atherogenic ( 51 ). Although PUFA lipid species are more easily oxidized than their saturated and monounsaturated counterparts ( 52,53 ) and ox-CE species have been identifi ed in human tissue samples from endarterectomies ( 28 ), no arterial ox-CEs were detected in our study, despite signifi cant enrichment of circulating and tissue lipids with by guest, on www.jlr.org Downloaded from large decrease in hepatic TG content does not necessarily result in decreased TG secretion.…”
Section: Downloaded Frommentioning
confidence: 99%